Manipulation robot system based on visual guidance for sealing blocking plate of steam generator. Issue 2 (1st February 2016) - Duan, Xingguang; Wang, Yonggui; Liu, Qingsong; Li, Meng; Kong, Xiangzhan
Abstract : To reduce labor intensity and irradiation exposure time inside the steam generator during the maintenance period of the nuclear power plant, a blocking plate manipulation robot system, including manipulation robot and pneumatic control console, is developed as an automatic remote-control tool to help staff to complete sealing steam generator primary pipes. The manipulation robot for fastening/loosening bolts utilizes visual guidance for target position, and the recognition algorithm is exerted to extract the bolt center coordinate values from image captured by camera in the procedure. The control strategy based on the position and current feedback is proposed for single bolt operation and whole bolts automatic operation. Meanwhile, the virtual interactive interface and remote monitoring are designed to improve the operability and safety. Finally, the relative experiments have verified the work effectiveness and the future work would be discussed.